Analysis of Use Formwork and Slipform Pavers in Making Concrete Barrier on Toll Road Project - Akhmad Taufik Aditama; Nina Saraswati; Puthut Satriawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
The making of concrete barrier on the KAPB Toll Road Project Package II Section 1 still uses manual formwork. The use of manual formwork is considered easier to implement, but less efficient because concrete barrier in the form of prototypes should be done practically. Innovation in the field of construction has created Slipform Paver to print concrete barrier. Slipform pavers are believed to be able to produce better productivity than manual formwork. This study analyzed productivity, work duration and costs in the use of molding concrete barrier as an effort to accelerate work. Observations on the making of concrete barrier were carried out in one cycle time from land preparation to finishing the work. Concrete barrier made with manual formwork use readymix concrete FC 20 slump + 10 cm, while slipform pavers use readymix concrete FC 20 slump 4-5 10 cm. The results of the study showed that in making concrete barrier the use of slipform pavers can accelerate the completion of work by up to 46.01% and save costs by 14.3% compared to using manual formwork. In working on all concrete barrier using manual formwork can be done, but requires additional resources so that it can be completed on time.